Legal framework supporting human security - Marsili, M.; Hughes, D. (Human security: Frameworks, concepts, actors and challenges in relevance to NATO, 2024)
Human security was written into the NATO strategic concept for the first time in 2022. Shortly after, NATO produced its “Approach and Guiding Principles for Human Security”. As such, human security has been put on the Alliance’s agenda. Conducting sound research on the concept is of outmost timely relevance as several questions remains unanswered when it comes to what human security will mean for the Alliance. The Exploratory Team (ET) 201 on Human Security (HFM-ET-201) has in the period of 2022-2023 discussed the relevance and development of human security in NATO. This report documents these discussions. The report covers why human security matters for NATO, legal and theoretical frameworks, human security and other concepts such as climate change and Women, Peace and Security (WPS), and human security and other actors such as the United Nations, European Union, United Kingdom, CIMIC and NATO itself. Lastly, the report addresses barriers for change before making suggestions for further research on human security in a NATO context.